Multicenter assessment of the reproducibility of volumetric radiofrequency-based intravascular ultrasound measurements in coronary lesions that were consecutively stented - Huisman, Jennifer (Springer Netherlands, 2012)
To assess in a multicenter design the between-center reproducibility of volumetric virtual histology intravascular ultrasound (VH-IVUS) measurements with a semi-automated, computer-assisted contour detection system in coronary lesions that were consecutively stented. To evaluate the reproducibility of volumetric VH-IVUS measurements, experienced analysts of 4 European IVUS centers performed independent analyses (in total 8,052 cross-sectional analyses) to obtain volumetric data of 40 coronary segments (length 20.0 ± 0.3 mm) from target lesions prior to percutaneous intervention that were performed in the setting of stable (65%) or unstable angina pectoris (35%). Geometric and compositional VH-IVUS measurements were highly correlated for the different comparisons. Overall intraclass correlation for vessel, lumen, plaque volume and plaque burden was 0.99, 0.92, 0.96, and 0.83, respectively; for fibrous, fibro-lipidic, necrotic core and calcified volumes overall intraclass correlation was 0.96, 0.94, 0.98, and 0.99, respectively. Nevertheless, significant differences for both geometrical and compositional measurements were seen. Of the plaque components, fibrous tissue and necrotic core showed on average the highest measurement reproducibility. A central analysis for VH-IVUS multicenter studies of lesions prior to PCI should be pursued. Moreover, it may be problematical to pool VH-IVUS data of individual trials analyzed by independent centers.